Организационно-правовой аспект административного надзора в сфере газоснабжения - Гурина, О.; Gurina, O. (Східноєвропейський національний університет імені Лесі Українки, 2015)
В статье исследуются надзорные функции по обеспечению надежной и безопасной эксплуатации систем газоснабжения. Частично указанные функции реализуются газоснабжающими организациями. В целях совершенствования управленческой деятельности в сфере газоснабжения, устранения правовых коллизий, представляется целесообразным передать публичные функции РУП-облгаз в части реализации надзорных полномочий органам государственного энергетического надзора Республики Беларусь. In the article supervising functions on ensuring reliable and safe operation of systems of gas supply have been investigated. During the Soviet period the mentioned functions were carried out by bodies of the state gas supervision. At the present stage in Republic of Belarus the appropriate specialized supervisory authority is actually absent. At the same time functions on ensuring reliable and safe operation of systems of gas supply are partially carried out by the gas supplying organizations. Studying of their legal status allowed us to reveal a number of problems in law-enforcement practice. One of the ways of their overcoming can be a transfer of publicly significant functions of the gas supplying organizations regarding realization of supervising powers to state energy control and supervision bodies of Republic of Belarus. The offered transformations will not only increase efficiency of activity in the sphere of ensuring reliability and safety of systems of gas supply by its streamlining within functioning of bodies of the state energy control and supervision, but they will not lead to increase in number of supervisory authorities and additional expenses from the budget either.
Organizational and Legal Aspect of Administrative Supervision in the Sphere of Gas Supply
Keywords: административный надзор; органы государственного газового надзора; газопоставляющая организация; публично значимые функции; газоснабжения; administrative supervision; bodies of the state gas supervision; as supplying organizations; publicly significant functions; gas supply